2006
DOI: 10.1242/dev.02566
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin is required for dendritic morphogenesis and synaptic terminal organization of retinal horizontal cells

Abstract: Dendrite morphology of neurons provides a structural basis for their physiological characteristics, and is precisely regulated in a cell type-dependent manner. Using a unique transposon-mediated gene transfer system that enables conditional and cell-type specific expression of exogenous genes, we investigated the role of cadherin on dendritic morphogenesis of horizontal cells in the developing chicken retina. We first visualized single horizontal cells by overexpressing membrane-targeted EGFP, and confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 55 publications
2
46
0
Order By: Relevance
“…N-cadherin mediates neurite elongation, as shown by in vitro (35,204,356) as well as in vivo (202,284,342) studies. Neurite outgrowth activity was also reported for R-cadherin, E-cadherin, cadherin 7, and cadherin 11 (14,28,40,240,241,278).…”
Section: Neurite Elongation and Branchingmentioning
confidence: 87%
See 2 more Smart Citations
“…N-cadherin mediates neurite elongation, as shown by in vitro (35,204,356) as well as in vivo (202,284,342) studies. Neurite outgrowth activity was also reported for R-cadherin, E-cadherin, cadherin 7, and cadherin 11 (14,28,40,240,241,278).…”
Section: Neurite Elongation and Branchingmentioning
confidence: 87%
“…For example, in retinal horizontal cells, N-cadherin defines the dendritic field size through the control of the attachment of their dendritic processes to photoreceptor cells (342). Ncadherin is also important for CA3 dendrite arborization in the hippocampus (30).…”
Section: Neurite Elongation and Branchingmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a few glycoproteins have been identified that play structural roles in triad synapses, such as dystrophin (Pilgram et al, 2010), retinoschisin (Johnson et al, 1996), and pikachurin (Sato et al, 2008), but these proteins are synthesized by either photoreceptors or bipolar cells. However, in chick horizontal cells, N-cadherin is required for dendrite morphogenesis and subsequent synapse formation with photoreceptor cells (Tanabe et al, 2006). Whether N-cadherin also plays a role in synapse maintenance remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…Xenopus retinal ganglion cells expressing a dominant negative N-cadherin fail to generate dendrites (Riehl et al, 1996), and chick horizontal cells show reduced arbor size (Tanabe et al, 2006). N-cadherin promotes dendritic outgrowth in hippocampal neurons (Esch et al, 2000), zebrafish amacrine cells require N-cadherin to arborize appropriately (Masai et al, 2003), and DN-cadherin restricts dendritic arbors that are generated by olfactory projection neurons in Drosophila (Zhu and Luo, 2004).…”
Section: Cadherins and Dendritic Arborsmentioning
confidence: 99%